2000
DOI: 10.1017/s0016756800003538
|View full text |Cite
|
Sign up to set email alerts
|

When a cosmic impact strikes the sea bed

Abstract: Most bolides that collide with the Earth hit the sea. Limited knowledge about marine-target impacts hampers predictions about their perilousness. This study presents geological features that are particular to craters formed at sea. The features are most likely a result of the influence of the target on the cratering process. Marine-target craters form only if the target sea is shallow enough to admit sufficient kinetic energy into the sea bed. When the crater diameter is large compared to the water depth, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
150
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(156 citation statements)
references
References 33 publications
6
150
0
Order By: Relevance
“…This sea had its deepest parts to the west of the Lockne impact site where a foredeep was developing in front of the approaching Caledonian orogen. The Tvären impact would have occurred at a location with a water depth estimated to have been about 100-150 m (Ormö and Lindström 2000), possibly in the lower range as discussed in this paper.…”
Section: General Description Of the Studied Cratersmentioning
confidence: 82%
See 1 more Smart Citation
“…This sea had its deepest parts to the west of the Lockne impact site where a foredeep was developing in front of the approaching Caledonian orogen. The Tvären impact would have occurred at a location with a water depth estimated to have been about 100-150 m (Ormö and Lindström 2000), possibly in the lower range as discussed in this paper.…”
Section: General Description Of the Studied Cratersmentioning
confidence: 82%
“…There is structural and stratigraphic evidence that deposition took place below hurricane wave base (Lindström 1963(Lindström , 1971(Lindström , 1984, which suggests a depth below 100 m. 2. For resurge to have generated a single massive deposit that settled out of suspension, the water depth should have been greater than the order of tens of meters (Ormö and Lindström 2000). 3.…”
Section: Stratigraphic and Environmental Setting Of The Brecciasmentioning
confidence: 99%
“…Marine-target impact craters represent ∼20% of known craters, a number that is much too low given that more than two-thirds of the Earth's surface is covered by water. This is attributed mainly to plate tectonic destruction processes, sparsity of detailed seismic reflection data from deep-water regions, and the difficulty in identifying buried or exposed submarine craters (e.g., Ormö and Lindström 2000;Dypvik and Jansa 2003). The sparcity of marine craters can be also ascribed to the burial of marine craters by post-impact sediments.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, if γ > 1, the water layer does not affect the cratering process significantly; these impacts are called shallow water impacts (SWIs). However, the final crater morphology may still differ from crater structures on land (Shuvalov and Trubestkaya 2002;Ormö and Lindström 2000). In between these two extreme cases (0.1 < γ < 1), the water column has a significant influence on crater formation (Shuvalov and Trubestkaya 2002;Weiss et al 2006).…”
Section: Cratering Mechanics and Wave Generationmentioning
confidence: 99%
“…Ormö and Lindström (2000) showed that there are unique geological features of impact craters generated at the ocean bottom. To form such craters, the impactor must penetrate through the water column and modify the solid strata underneath.…”
Section: Introductionmentioning
confidence: 99%